Factor Affecting Indonesian Charcoal Export To China - Nurul Hidayah (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2023)
The purpose of this study was to determine the effect of Gross Domestic Product (GDP) and the Rupiah Exchange Rate on the Volume of Indonesian Shell Charcoal Exports to China. The data used in this study is secondary data that is time series. In this study, the method used as an analytical tool is Ordinary Least Square (OLS) to determine changes in the value of the dependent variable, namely the Export Volume of Indonesian Shell Charcoal which is influenced by the independent variable, namely China's Gross Domestic Product (GDP) and Exchange Rates using multiple linear regression techniques. The method used in this research is descriptive quantitative, namely explaining the results of computerization using the E-Views 9 program.The results of the analysis show that simultaneously China’s GDP and the Exchange Rate have a significant effect on the Export Volume of Indonesia Shell Charcoal to China in 2001 – 2020. The results of the analysis show partially China’s Gross Domestic Product (GDP) had no effect on the Export Volume of Indonesia Shell Charcoal to China in 2001 – 2020 and the Exchange Rate had a positive and significant effect on the Export Volume of Indonesia Shell Charcoal to China in 2001 – 2020.The result of the Coefficient of Determination (R2) is carried out to see how big the proportion of the influence of the independent variable on the dependent variable is. In this case, the value of the coefficient of determination used is Adjusted R-Squared which is the coefficient of determination that has been corrected by the number of variables and sample size. It is known that the Adjusted R-Squared value is 0,366601 or 36.66%. This indicates that a 36.66% change in the Volume of Indonesian Shell Charcoal Exports to China was caused by changes in China's Gross Domestic Product (GDP) and the Exchange Rate. While the remaining 63.34% changes in the Volume of Indonesian Shell Charcoal Exports to China were caused by changes in other variables that were not used in the study.